The Effectiveness of Health Promotion on the Tobacco Fatwa Issued by Tarjih and Tajdid Council of Muhammadiyah - Shubhi Mahmashony Harimurti (IJISH (International Journal of Islamic Studies and Humanities), 2022)
Given the sensitive issue of tobacco fatwa, there is a need to promote this fatwa through a health promotion. This study aims to analyze the effectiveness of health promotion by the Fatwa and Islamic Research Council of the Central Board of Muhammadiyah regarding the tobacco fatwa that bans smoking. In addition, it also focuses on the portion of health problems compared to other issues in the tobacco fatwa. This research aims (1) To analyze the effectiveness of health promotion by The Fatwa and Islamic Research Council regarding the fatwa on smoking prohibition. (2) To analyze the portion of health problems compared to other issues in the discussion of smoking prohibition fatwa by The Fatwa and Islamic Research Council. This is field research that was conducted using questionnaire and interview methods including a Focus Group Discussion and applying a qualitative and quantitative approach. The research reveals that the Fatwa and Islamic Research Council has not collaborated with related institutions in providing health promotion to its citizens. It is also revealed that the health issue has received a proportional highlight in the fatwa, but the concern is that many Muhammadiyah members are unaware about this fatwa.